XIAP 3′-untranslated region serves as a competitor for HMGA2 by arresting endogenous let-7a-5p in human hepatocellular carcinoma - Wen-Yong Wu; Si-Qi Tao; Xiao-Nan Wang; Peter E Lobie; Zheng-Sheng Wu (Tumor Biology, 2017)
X-linked inhibitor of apoptosis protein functions as an intrinsic regulator of apoptosis by inhibition of caspase activity and possesses a pivotal role in human cancer development and progression. A growing body of literature has demonstrated that microRNAs lead to the degradation or translational repression of messenger RNAs by binding to the non-coding region of messenger RNA at the 3′-untranslated region. Here, we revealed that the expression of HMGA2 is upregulated with X-linked inhibitor of apoptosis protein after transfection of X-linked inhibitor of apoptosis protein 3′-untranslated region in hepatocellular carcinoma cells, suggesting that X-linked inhibitor of apoptosis protein 3′-untranslated region serves as a competitor for microRNAs and prevent the co-targeted messenger RNA, HMGA2, from being suppressed. We further identified that let-7a-5p could bind to both the X-linked inhibitor of apoptosis protein 3′-untranslated region and HMGA2 3′-untranslated region. Moreover, we demonstrated that the forced expression of X-linked inhibitor of apoptosis protein 3′-untranslated region increases the oncogenicity of hepatocellular carcinoma cells in vitro. Cell functional analyses were performed to examine the association of HMGA2 status and X-linked inhibitor of apoptosis protein 3′-untranslated region. We have also measured the functional readout of let-7a-5p and HMGA2, an assay often employed to provide substantial evidence for the effects of X-linked inhibitor of apoptosis protein 3′-untranslated region on hepatocellular carcinoma cells. In general, our findings suggest that X-linked inhibitor of apoptosis protein 3′-untranslated region serves as a competitive endogenous RNA for HMGA2 to activate hepatocellular carcinoma progression by arresting endogenous let-7a-5p.